2019
DOI: 10.1097/ppo.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Management of T-Cell Engaging Immunotherapy Complications

Abstract: The advent of T-cell–mediated immunotherapy has led to a new era in the treatment of relapsed, refractory B-cell lymphomas and leukemias. Chimeric antigen receptor T-cell and engineered T-cell receptor therapies have demonstrated impressive efficacy in treating refractory disease. The principal toxicities of these therapies include cytokine release syndrome and immune effector cell–associated neurotoxicity syndrome (ICANS), but others exist as well. Cytokine release syndrome and ICANS are typically acute event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…51 ICANS can occur concomitantly with CRS, after resolution of CRS or independently of CRS. 31,74,88 In the latter case, neurological symptoms tend to be mild. 100 Usually, ICANS presents 4-5 days after CAR T-cell administration, 101 but delayed ICANS occurring 3-4 weeks after CAR T-cell treatment has also been reported.…”
Section: Immune Effector Cell-associated Neurotoxicity Syndromementioning
confidence: 98%
See 4 more Smart Citations
“…51 ICANS can occur concomitantly with CRS, after resolution of CRS or independently of CRS. 31,74,88 In the latter case, neurological symptoms tend to be mild. 100 Usually, ICANS presents 4-5 days after CAR T-cell administration, 101 but delayed ICANS occurring 3-4 weeks after CAR T-cell treatment has also been reported.…”
Section: Immune Effector Cell-associated Neurotoxicity Syndromementioning
confidence: 98%
“…40 For patients with clinical deterioration despite at least two doses of tocilizumab as well as for patients with increased risk of severe CRS and neurotoxicity, additional treatment with corticosteroids should be considered. 47,53,74 In contrast to tocilizumab, corticosteroids exert non-specific anti-inflammatory effects that abrogate inflammation by inhibiting CAR T cells as well as bystander immune cells. 75 Although initial studies reported reduced expansion and lacking persistence of CAR T cells in patients who received corticosteroids, 3 early steroid use in subsequent studies has not been associated with detrimental effects on clinical remission rates or CAR T cell persistence.…”
Section: Management Of Crsmentioning
confidence: 99%
See 3 more Smart Citations